On the electrical properties of distinct Eu3 + emission centers in the heterojunction GaAs/SnO2 - De Freitas Bueno, Cristina [UNESP]; De Andrade Scalvi, Luis Vicente [UNESP] (Elsevier, 2016)
GaAs/SnO2:2%Eu heterojunctions are deposited by resistive evaporation and sol-gel-dip-coating techniques respectively, with the top layer thermally annealed at different temperatures. The sample annealed at 200 °C/1 h has a much higher conductivity and a lower deepest level (79 meV) than the sample annealed at 400 °C/20 min, for which the deepest level value is 98 meV. The decay of photo-induced current at room temperature for these heterojunctions shows a decay of 48.8% from the initial value for a sample annealed at 200 °C/1 h, compared to a decay of 54.2% from the initial value for a sample treated at 400 °C/20 min. The excitation source has a broad band with energy lower than 1.65 eV, assuring that no electron-hole pair is generated in the SnO2 (top) layer. The data fitting seems to indicate that, although the grain boundary scattering dominates the mobility, the inclusion of time dependent terms is needed, such as multi-center capture or ionized impurity scattering. Photoluminescence data shows that the main Eu3 + transition changes from 5D0 → 7F2 (related to ions located at asymmetric sites such as boundary layer) to 5D0 → 7F1 (related to ions located at symmetric sites), as the annealing temperature is increased.
Keywords: Electrical properties; Gallium arsenide; Heterojunction; Photoluminescence; Tin dioxide